2011
DOI: 10.3174/ajnr.a2837
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Abnormalities in Patients with Parkinson Disease: A Comparative Voxel-Based Analysis Using T1-Weighted MR Imaging and Magnetization Transfer Imaging

Abstract: BACKGROUND AND PURPOSE:In PD, tissue damage occurs in specific cortical and subcortical regions. Conventional MR images have only limited capacity to depict these structural changes. The purpose of the current study was to investigate whether voxel-based MT imaging could indicate structural abnormalities beyond atrophy measurable with T1-weighted MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
(36 reference statements)
2
19
1
Order By: Relevance
“…Most previous studies [1214] found that the MTR of the substantia nigra was lower in PD patients than in healthy people, and no differences were discovered in the globus pallidus, putamen or caudate. The MTR changes in the red nucleus seemed inconsistent on the basis of previous results.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Most previous studies [1214] found that the MTR of the substantia nigra was lower in PD patients than in healthy people, and no differences were discovered in the globus pallidus, putamen or caudate. The MTR changes in the red nucleus seemed inconsistent on the basis of previous results.…”
Section: Discussionmentioning
confidence: 96%
“…The MTR changes in the red nucleus seemed inconsistent on the basis of previous results. Both Tambasco et al [12] and Anik et al [13] found a lower MTR value in PD patients, while Morgen et al [14] found no difference between PD patients and controls. However, we did not find any significant differences for the MTR(15.6 ppm) in any of the regions between normal controls and PD patients (Table 1), and this inconsistency may be due to the lower RF saturation power (2 μT) used in our protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD pathology may lead to dysfunction and shrinkage of the amygdala and possibly with that the development of anxiety symptoms. There is some evidence from neuroimaging studies suggesting that amygdala volume is reduced in patients with PD compared with matched healthy controls34 35 and that (surgical) damage to the amygdala is associated with the development of anxiety 36 37. On the other hand, anxiety may itself cause of shrinkage of brain structures through overactivation of the hypothalamus-pituitary-adrenal axis (HPA) stress axis 38.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in methodologies and experimental designs may account for a substantial amount of the heterogeneity reported. Beside the brain segmentation methods, the Voxel-based analyses are also a technique used for volume estimation (Morgen et al, 2011).…”
Section: White Matter Volume Of Sensory Cortexmentioning
confidence: 99%